Pain and anxiety experiences of South African adult burn injury patients during physiotherapy management - L.D. Morris; Q.A. Louw (AOSIS, 2010)
A dequate management of procedural pain during physiotherapy management plays an important role in building a trusting relationship betweenthe burn victim and the physiotherapist, and in ensuring desirable functional outcomes. However, the burn pain management regimens currently utilized inburn units, primarily consist of traditional pharmacologic analgesics which areassociated with numerous side-effects and alone are often reported as inadequateto alleviate procedural pain, warranting safer and effective adjunct therapies.Prior to the introduction and implementation of adjunct therapies into a developing world, it is imperative that the current situation in a burn unit, in terms of whether or not the pain management regimens in place are adequate, is first assessed, due to cost concerns. The following short report exemplifies the pain and anxiety experiences of a small number of burn injury patients during physiotherapy at the Tygerberg Hospital adult burn unit, South A frica.  It was hypothesized that the results of this study would underpin whether adult burn injury patients in a developing countryrequire adjunct therapies during physiotherapy management to supplement traditional pharmacologic analgesics inmanaging their procedural pain and subsequent anxiety.